Insight into Drugs Induce Liver Toxicity - Zageer, Dheaa Shamikh; Hantoosh, Sundus Fadhil (Insight into Drugs Induce Liver Toxicity, 2021)
The liver is a critical organ in the human body. It performs an array of functions that help support metabolism, immunity, digestion, detoxification, vitamin storage among other functions. Detoxification is proposed that non-reactive compounds could be biotransformed in two phases: functionalization, which uses oxygen to form a reactive site, and conjugation, which results in addition of a water-soluble group to the reactive site. These two steps, functionalization and conjugation, are termed phase I and phase II detoxification, respectively. The result is the biotransformation of a lipophilic compound, not able to be excreted in urine, to a water-soluble compound able to be removed in urine. The liver is the major organ actively involved in metabolism and detoxification of drugs and xenobiotics. Drug metabolism can be divided into three phases. The phase I drug oxidation involves superfamily of CYP monooxygenases. Phase I reactions may activate prodrugs to the active forms and metabolize xenobiotics to nontoxic compounds, but in some, increases toxicity of the metabolites. The phase II reactions are conjugation reaction including sulfation, methylation, and glucuronidation to further increase the solubility of oxidized metabolites, which are secreted through the phase III drug transporters located in the membranes of hepatocytes, intestine cells, kidney, and other tissues for excretion out of the body. A drug-induced liver injury (DILI) is defined as a liver injury caused by exposure to a drug or a non-infectious toxic agent with a variable degree of organ dysfunction. From a pharmacological point of view, it is possible to identify two types of DILI: dose-dependent and dose-independent or idiosyncratic. Dose-dependent DILI, also known as direct toxicity, is predictable, reproducible and develops with short latency after the consumption of a dose exceeding a known toxic threshold. Damage entity is proportional to administered dose. Idiosyncratic DILI, instead, is unpredictable and usually develops at therapeutic doses. The damage amount is not always proportional to administered dose and the time to damage’s onset can vary widely. Clinical presentation of DILI can comprise mitochondrial impairment, inhibition of biliary efflux, lysosomal impairment, endoplasmic reticulum stress, production of reactive metabolites leading to chemical stress, oxidative stress, and protein modification, and in addition, clinical presentation of DILI includes triggering of the innate and adaptive immune responses and causing activation of cytotoxic T cells and B cells, and exaggerated production of pro-inflammatory cytokines. All these presentations can result in liver damage. Phenotypes of DILI involve acute hepatic necrosis, enzyme elevations, acute hepatitis, cholestatic hepatitis, mixed hepatitis, chronic hepatitis, bland cholestasis, acute fatty liver disease, lactic acidosis, hepatic failure, nonalcoholic fatty liver disease, sinusoidal obstruction syndrome, and nodular regenerative hyperplasia.